Listeriosis in Australia - January to July 2018 - Arpita Das (University of New South Wales, 2019)
A national outbreak of listeriosis is linked to the consumption of rockmelon (cantaloupe) originating from New South Wales and has affected other states of Australia, including Victoria, Queensland and Tasmania.The outbreak began after 10 elderly people were diagnosed with Listeriosis after consuming cantaloupe and became ill between 17 January and 9 February, 2018 .